Introducing an inquiry-based experiment-integrated science game for elementary students: the shadow races game. (3rd April 2019) - Bayir, Eylem
Abstract: This article introduces a science game which can be used for innovative teaching and as an assessment tool. The Shadow Races Game is designed for first and second grade students to learn the phenomenon of shadow through inquiry-based activities and questions that require the children to apply inferences from those activities. In this amusing board game, students will discover the relationship between light, objects and shadows using familiar objects.